EFEKTIFITAS PENGGUNAAN MEDIA PUZZLE DALAM MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN PECAHAN SEDERHANA BAGI ANAK KESULITAN BELAJAR - Vita Marta Sari (Jurnal Penelitian Pendidikan Khusus, 2014)
The background of this research by the problems that’s research find in SDN 08 Padang Besi. Kids learning dissabiities who have not been able o understand the concept of simple fraction, could not say, show and write fraction, the numerator and denominator do no know, have not been able to match fractions fractional image, have not been able to create and image fractions. Based on this research aim to improve children’s ability to understand the concept of simple fractions by using puzzle Jenis Media used was an experimental study in a single subject research with this study is the cild A-B-A. subject dissabilitis a child class 3 SD. Data learning thrd grade obtained by using test and observation, data analisis is a visual analysis of graphic data obtained from observation on the condition of A- B – A2. Condisi  baseline before granted intervention with eight sessions, A = 0%, the intervention condition 12 meetings, B= 90 %, and in the baseline condition after not using the media puzzle five meetings, A= 100 %. Result of the study that the media puzzle is effective in improving the ability to know the simple concept of fractions for kids learning disabilities in SDN 08 Padang Besi. Researchchers suggest to the teacher that the media puzzle used as an alternative in learning mathematic, especially in learnin recognize simple fractions.